The impact of foreign direct investment on total factor productivity: The case of Vietnam - Ngoc, Minh Ngo (Journal of Social Economics Research, 2025)
The purpose of this study is to evaluate the impact of spillover effects from foreign direct investment (FDI) on domestic supporting industry businesses in Vietnam. To this end, the paper uses the translog production function and addresses the endogeneity problem with the fixed effects method, followed by a random-effects model utilizing data from the enterprise survey conducted during the period of 2018-2022. The findings indicate that while intra-industry FDI enterprises have a negative impact, downstream FDI enterprises have a favorable impact. Domestic businesses with greater human resources will be better able to withstand downstream effects. Some policies that should be implemented in the near future include increasing the spillover effects from downstream FDI enterprises, reducing competitive pressure from FDI enterprises in the same industry, and promoting the role of human resources.